Development of a Practical Tool for Linear Momentum Collisions Using a Microcontroller - Huda, Itmamul; Girei, Musa Mohammed; Keizi, Farokh (Journal of Educational Technology and Learning Creativity, 2023)
Purpose of the study: This research aims to develop a linear momentum collision practical tool with a microcontroller so that the results obtained are more accurate, the time used is more efficient and the experiments carried out are more varied. Methodology:This research is R & D research with development procedures, namely the potential and problem stages, data collection, product design, design validation, product design revision, product testing, final product. The subjects in this research were 2 media expert lecturers, 2 material expert lecturers, 20 pre-research students, 4 limited test students and 38 broad test students. Data collection techniques use observation, documentation and questionnaire techniques. The data analysis technique used is descriptive qualitative and quantitative . Main Findings: The results of research on the development of linear momentum collision practical equipment with a microcontroller obtained a value from material expert tests of 3.8 with an ideal percentage of 94%, from media expert tests of 3.91 with an ideal percentage of 97.5%, from limited field tests of 3.93 with an ideal percentage of 78.75% and from tests The wide field is 3.85 with an ideal percentage of 77%. Novelty/Originality of this study: The novelty of this research is the development of a linear momentum collision practical tool whose instrument part is for measuring the speed of objects determined using an ATmega 16 microcontroller and an ultrasonic sensor as a distance sensor. This learning media can be useful in improving the physics learning process to be more meaningful